Development of Systematic Sustainability Assessment (SSA) Tool for Enviromental Management in Malaysia Hydroelectric Project - Nur Soliha, Sahimi; Faiz, Mohd Turan; Kartina, Johan (Universiti Malaysia Pahang, 2017)

(untitled)
Nowadays, there are many significant impacts due to hydropower development such on society or community, environmentally and economically. These impact may go more seriously even across the nation. As one of the latest of hydropower development in Malaysia, the Tekai Project has been paying attention from the commencement stage in thisresearch. To remain competitive to other industries in Malaysia such in manufacturing, automotive and other else, an implementation of sustainability is very important to growth their business performance. In addition, sustainability is vital to Bursa Malaysia Securities Berhad under their listing requirements. Therefore, this study aims to develop a sustainability assessment practice for hydropower sector in Malaysia context by referring to Department of Environment (DOE) requirement, Green Project Management (GPM) P5 concept and State Council guideline. The sustainability practice adopted in hydropower project generally follow GPM P5 concept which cover society (people), environmentally (planet), economically (profit) and also process and product viewpoint. As a result, a satisfactory from the state council or auditor to the project standard will be achieved. In addition, this study, will contribute a number of factors towards sustainability performance of hydropower sector in Malaysia including provide a sustainable integrated reporting toward the project and provide a new sustainability approach to project manager.